Kajian Komunikasi Massa menurut Perspektif Periodisasi - Mulyanti Syas (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The study of mass communication concepts in this literary refers to the opinion Chaffe and Metzger are evaluating this concept to three important conceptualization about mass communication, that is: 1) the mass communication media as an institution 2) Mass communication as a social problem, and c) Mass communication as an academic study. Concepts related to other mass media is gatekeeping. Kurt Lewin states a theory about group dynamics and the concept of gatekeeper.